Аналіз впливу неточності виготовлення діаметрів стрічкопровідних циліндрів на натяг стрічки в рулонних ротаційних машинах - Луцків, І. М. (Видавництво Національного університету «Львівська політехніка», 2004)
A task of construction of mathematical model of the conductribbon system, which takes into account influencing inaccuracy of making diameters of conductribbon cylinders on pull of ribbon on areas is considered. Results of computer simulation are conducted.